The Explanatory Component of Moral Responsibility - Björnsson, Gunnar; Persson, Karl (Noûs (Bloomington, Indiana), 2012)
The fact that changes of focus affect intuitions of responsibility raises questions: On what factors should we focus our attention? What focus makes for reliable intuitions? Clearly, more arguments are needed; what is far from clear is what sort of argument we should be looking for. This paper approaches the problem from a new angle. It would be easier to determine what to think about moral responsibility if we were clearer about why we react the way we do to these arguments, and why our reactions vary.